O odwadze bycia bezsilnym - Mariusz Sztuka (Jesuit University Ignatianum in Krakow, 2017)
The article takes up the issue of control as a category of explaining behaviours of deviant character. Reﬂ ection to date as well as research achievements within this scope have situated the concept of control in the context of social system functioning, or reduced it to certain personal characteristics, generally described as a sense of perpetration. On the grounds of popular associations, these characteristics are connected with such traits as: self-control, strong character, will power, thus constituting the condition for self-education activities, including self-correction activities. Attempts to apply such viewpoint for the analysis of complex educational and corrective situations consistently frequently encounter a substantial obstacle, deﬁ ned here as a paradox of control, which is that conviction about the ability to control one's own situation may entail as many opportunities as dangers